VIOLATION AND COMPLIANCE OF PRINCIPLE OF CIVILITY IN THE BOOK "DEATH LAUGH (THE WAY OF SOEHARTO)". AUTHORSHIP OF INDONESIAN PEOPLE: DIGITAL PRAGMATIC-BASED STUDIES OF CORPUS - Arijalurahman Arijalurahman (Proceeding of International Conference on Art, Language, and Culture, 2017)
The main issues studied in this research are violations and compliance with the principle of politeness in the book " death laugh (the way of Soeharto) by the Indonesian people". The aim of this study; (1) classifies and describes categories of violations of the principle of politeness in the book "death laugh (the way of Soeharto) accompanied by explanations of the causes of the offenses arising; (2) to classify and describe the categories of compliance with the principle of politeness in the book " death laugh (the way of Soeharto) (the way of Soeharto) accompanied by explanation of the causes of adherence. Given this research is a literature study, then the method of data collection in this study using the method refer (observation or observation) combined with digital corpus program. The digital corpus that researchers use is the "AntConc" program. The working principle of the program finds lexem, words, and phrases, which contain elements of violation and compliance with the principle of politeness. Data that has been identified in AntConc will be recorded manually. It is then analyzed by replacing the initial data element and inserting the new data element as a comparison, then described with explanation as the cause of the breach and compliance arises. The guidelines for classifying abuses and adherence in the book are based on Leech's politeness principle divided into five maxims (maxim of wisdom, dignity, respect, simplicity, and consensus). Based on the results of data analysis, there is a violation and compliance of the principle of politeness in the book " death laugh (the way of Soeharto). Violations and compliance occur in almost all of the maxims, including in the maxims of wisdom, generosity, appreciation and consent.